Numerical analysis of composite steel and concrete beams exposed to fire - Carlos Emerick Nunes; Macksuel Soares de Azevedo (REM: International Engineering Journal)
Abstract This article focuses on numerical thermos-structural behavior evaluation of composite steel and concrete beams under fire conditions. Several models of composite beams are analyzed, changing the following parameters: steel beam, span length, load level, slab thickness, concrete and steel strength. The numerical models, validated by experimental results of other authors, were developed using the finite element method on software ANSYS and the language APDL. It was observed that the structural load level is the main parameter that affects the structural behavior of composite steel and concrete beams under fire conditions.